(untitled) (Research, Society and Development, 2020)
The indigenous population in Brazil has been growing in recent years, it is estimated that the reach of this population is greater than 900 thousand declared natives and are located in 305 ethnic groups and 274 languages. Exclusive breastfeeding up to 6 months of age is recommended and healthy complementary feeding should be introduced after 6 months. However, it is understood that indigenous peoples have a complex health circumstance that is directly related to social, economic and environmental changes, a historical process that has aggravated health conditions. This study aimed to analyze through a literature review the impacts of breastfeeding and the introduction of complementary feeding in children up to 2 years old of indigenous peoples. The bibliographic search was carried out using the databases BIREME, LILACS, SCIELO, MEDLINE and articles published in the last ten years and national ones were selected. After reviewing the literature, it became evident that the duration of breastfeeding in indigenous populations is much shorter than that recommended by WHO. Therefore, impacting not only on the health of indigenous children, but also on the relationship of bonding, reception, admiration between mother and child.